Polyolefin porous membrane and method for manufacturing the same, battery separator, electrochemical device

KR103015870B1Active Publication Date: 2026-09-04SINOMA LITHIUM BATTERY SEPARATOR (NANJING) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020237024918
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-28
Filing Date
2023-04-25
Publication Date
2026-09-04
Estimated Expiration
2043-04-25

Smart Images

  • Figure 112023080079834-PCT00019_ABST
    Figure 112023080079834-PCT00019_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of separators for electrochemical devices, and discloses a polyolefin porous membrane, a method for manufacturing the same, a battery separator, and an electrochemical device. The polyolefin porous membrane of the present invention has a network fiber structure, and when observing an SEM image of the network fiber structure at 20,000x magnification, it has the following characteristics: (1) In a circle with a radius of 1000 nm, the fiber orientation result in the MD direction of a fiber with a fiber diameter > 15 nm satisfies R_MD, which is (R_MD)2 < 0.8; (2) In a circle with a radius of 1000 nm, the fiber orientation result in the TD direction of a fiber with a fiber diameter > 15 nm satisfies R_TD, which is (R_TD)2 < 0.8; therefore, the polyolefin porous membrane of the present invention can improve the stability of battery production and the safety of battery applications of the separator by realizing consistency in mechanical performance as a separator in a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] [Cross-reference of related applications]

[0002] The present invention claims priority to a PCT patent application filed on October 28, 2022, with the National Intellectual Property Administration of China as the receiving office, application number PCT / CN2022 / 128427, titled “Polyolefin porous membrane and method for manufacturing the same, battery separator, electrochemical apparatus,” all of which are incorporated into the present invention by reference.

[0003] The present invention relates to the technical field of separators for electrochemical devices, and in particular to a polyolefin porous membrane and a method for manufacturing the same, a battery separator, and an electrochemical device. Background Technology

[0004] The separator is a core component of lithium-ion batteries. Its primary role is to separate the anode and cathode to prevent short circuits, while simultaneously ensuring consistent electrolyte permeability and retention to provide channels for lithium-ion transport. Each performance characteristic of the separator directly determines the battery's interfacial performance and internal resistance, thereby influencing its charge / discharge and cycle performance.

[0005] The lithium-ion battery separator of the prior art is mainly a polyolefin porous separator, and the polyolefin porous separator has a three-dimensional structure that contains a large number of micro-through pores inside and supports a large number of pores with polyolefin as a framework, and the manufacturing method is mainly divided into dry stretching and wet stretching. Here, the dry method is a method of forming a polyolefin film and then stretching the film at a low temperature to form micropores, and microcracks occur between the thin sheets, which are the crystalline portions of the polyolefin, due to the stretching. The wet method is a method of mixing a polyolefin resin and a diluent at a high temperature where the polyolefin resin melts to form a single phase, and then separating the polyolefin and the diluent during the cooling process and extracting the diluent to form pores.

[0006] The wet method imparts mechanical strength and transparency through a stretching / extraction process after phase separation treatment, and by controlling stretching conditions such as speed, magnification, and temperature while stretching the polyethylene blank sheet formed into a sheet shape, the amorphous portion of the crystal structure is extended and microfibers are formed, while simultaneously forming micropores between the sheet-shaped layers. Compared to the dry method, the wet method has a thinner film thickness, uniform pore diameter, and superior physical performance.

[0007] In the document with publication number JP2005056851A, a microporous membrane of a laminate film is proposed. In order to reduce the thermal shrinkage rate of the separator in the TD direction (direction perpendicular to the machine, width direction), the manufacturing method does not perform stretching in the TD direction, so it can be said that there is no shrinkage in the TD direction; however, because a microporous membrane having extreme anisotropy with insufficient strength in the TD direction is formed through uniaxial opening in the MD direction (machine direction, length direction), unidirectional cracks can easily occur, for example, in battery crushing tests, impact tests, etc.

[0008] In the document with publication number JP2014141644A, a bidirectionally oriented porous polypropylene film is described in which the ratio of tensile strength in the MD direction to the TD direction is 0.9 or higher and less than 1.5. However, since the above polypropylene film is manufactured by dry processing, it has low air resistance, and further improvement of elongation at break and toughness is required.

[0009] A Chinese patent with publication number CN107250234B discloses a polyolefin microporous membrane, which is composed mainly of polypropylene, has a ratio of tensile strength in the MD direction to TD direction of 0.4 or more and 2.0 or less, and a ratio of elongation at break in the MD direction to TD direction of 0.6 or more and 1.7 or less, and can further improve impact resistance by adding additives that promote or inhibit crystallization of the polyolefin resin, nucleation agents, and crystallization retarders to make the pore structure of the polyolefin porous membrane uniform and fine.

[0010] Therefore, improving the performance of the separator is crucial for enhancing the safety performance of the battery. While conventional polyolefin porous separators can be maturely applied to lithium-ion batteries, current technology primarily focuses on the basic physical properties and physicochemical performance of the separator, paying less attention to the consistency of the microstructure. To improve the performance of wet separators in lithium-ion batteries, it is necessary to optimize performance in terms of microstructure and to optimize the isotropy of their mechanical performance.

[0011] The objective of the present invention is to provide a polyolefin porous membrane that, when used as a battery separator, can improve the stability of battery production by providing a battery with excellent safety.

[0012] The objective of the present invention is also to provide a method for manufacturing the above-described polyolefin porous membrane, wherein by controlling and reducing the difference in orientation during the stretching process of the separation membrane and controlling the molding temperature, a polyolefin porous membrane can be obtained in which the orientation of the microfiber structure is uniform and furthermore, the difference in macroscopic bidirectional mechanical performance is small.

[0013] The polyolefin porous membrane provided by the present invention is manufactured by wet stretching and has a network fiber structure;

[0014] When observing the SEM image of the above network fiber structure at 20,000x magnification, it has the following characteristics.

[0015] (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a diameter > 15 nm is (R_MD) 2 Satisfying <0.8, R_MD is obtained from Equation 1 below, and

[0016] Equation 1;

[0017] In the above equation, N is the quantity of fibers on the outermost surface within the observation area, each fiber is denoted by n, and θ n is the narrow angle between fiber n and the MD direction, and θ n It is obtained in a counterclockwise direction starting from the left direction in the MD direction, and the length value L of fiber n in μm units. n and cosθ n The product of is L n cosθ n and φ n is the diameter value of the fiber n in nm units.

[0018] (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a diameter > 15 nm is (R_TD) 2 Satisfying <0.8, R_TD is obtained from Equation 2 below, and

[0019] Equation 2;

[0020] In the above equation, N is the quantity of fibers on the outermost surface within the observed area, each fiber is denoted by n, and β n is a narrow angle with fiber n in the TD direction, and β n It is obtained in a counterclockwise direction starting from the upward direction in the TD direction, and the length value L of fiber n in μm units. n and cosβ n The product of is L n cosβ n and φ nis the diameter value of the fiber n in nm units.

[0021] Optionally, the provided polyolefin porous membrane is manufactured by wet stretching and has a network fiber structure;

[0022] When observing the SEM image of the above network fiber structure at 20,000x magnification, it has the following characteristics.

[0023] (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a diameter > 15 nm is (R_MD) 2 Satisfying <0.5, R_MD is obtained from Equation 1 below, and

[0024] Equation 1;

[0025] In the above equation, N is the quantity of fibers on the outermost surface within the observation area, each fiber is denoted by n, and θ n is the narrow angle between fiber n and the MD direction, and θ n It is obtained in a counterclockwise direction starting from the left direction in the MD direction, and the length value L of fiber n in μm units. n and cosθ n The product of is L n cosθ n and φ n is the diameter value of the fiber n in nm units.

[0026] (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a diameter > 15 nm is (R_TD) 2 Satisfying <0.5, R_TD is obtained from Equation 2 below, and

[0027] Equation 2;

[0028] In the above equation, N is the quantity of fibers on the outermost surface within the observed area, each fiber is denoted by n, and β n is the narrow angle between fiber n and the TD direction, and β nIt is obtained in a counterclockwise direction starting from the upward direction in the TD direction, and the length value L of fiber n in μm units. n and cosβ n The product of is L n cosβ n and φ n is the diameter value of the fiber n in nm units.

[0029] The above polyolefin microporous membrane also has the following characteristics.

[0030] Optionally, if the ratio of tensile strength in the MD direction to tensile strength in the TD direction is the MD / TD tensile strength ratio, then 0.8 ≤ MD / TD tensile strength ratio ≤ 1.2.

[0031] Optionally, if the ratio of the elongation at break in the MD direction to the elongation at break in the TD direction is the MD / TD elongation at break ratio, then 0.4 ≤ MD / TD elongation at break ratio ≤ 1.2.

[0032] Optionally, the thickness of the polyolefin porous membrane is 1 to 30 μm.

[0033] The present invention also provides a method for manufacturing a polyolefin porous membrane as described above, and the manufacturing method comprises:

[0034] Step 1: Mixing and extruding a polyolefin, a pore-forming agent, and an additive, wherein the mass ratio of the polyolefin in the mixture is ≥15% and the mass ratio of the antioxidant in the mixture is 0~0.5%; and, after biaxial high-temperature dispersion mixing and plasticizing, extruding through a die to produce a cast sheet;

[0035] Step 2: A step of stretching a cast sheet, wherein the temperature of the cast sheet material itself does not exceed 140℃ during the stretching process, the temperature difference between different points in the temperature field of the stretching area is less than 0.5℃, and the ratio of the stretching ratio in the MD direction to the stretching ratio in the TD direction during the stretching process, i.e., the MD / TD stretching ratio ratio, is 0.9 ≤ MD / TD stretching ratio ratio ≤ 1.1, thereby producing an oil film; and

[0036] Step 3: After extracting the oil film, a heat-setting treatment is performed, and during the heat-setting treatment, the original MD and TD stretching ratio relationship must be maintained, and the ratio of the stretching ratio in the MD direction and the stretching ratio in the TD direction of Step 2 is maintained through width-enlarging treatment during the heat-setting treatment.

[0037] Optionally, in step 2 above, the stretching ratio in the MD direction and the stretching ratio in the TD direction are both 5 times or more.

[0038] Optionally, the viscosity average molecular weight of the polyolefin is between 200,000 and 5 million.

[0039] Optionally, the pore-forming agent is one or more of white oil, paraffin oil, and polyethylene glycol.

[0040] Optionally, the additive in step 1 comprises an antioxidant, and the antioxidant is one or more of amines, sulfur-containing compounds, nitrogen-containing compounds, phosphorus-containing compounds, and organometallic salts.

[0041] The present invention also provides a battery separator comprising a polyolefin porous membrane as described above.

[0042] The present invention also provides an electrochemical device comprising a polyolefin porous membrane or a battery separator such as the above as a device for separating the positive and negative electrodes.

[0043] The present invention has the following beneficial effects.

[0044] The polyolefin porous membrane of the present invention can improve the stability of battery production and the safety of battery applications of the separator by achieving consistency in mechanical performance as a separator in a battery. Brief explanation of the drawing

[0045] To more clearly explain the technical solution means of the embodiments of the present invention, the drawings necessary for the embodiments are briefly introduced below. Since the drawings below represent only some embodiments of the present invention, they should not be considered as a limitation on the scope of the present invention, and those skilled in the art should understand that other related drawings can be obtained based on these drawings without the need to strive to create an inventive step. Figure 1 is a scanning electron microscope image showing the polyolefin porous membrane of Example 1. Figure 2 is a scanning electron microscope image showing the polyolefin porous membrane of Example 2. Figure 3 is a scanning electron microscope image showing the polyolefin porous membrane of Example 3. Figure 4 is a scanning electron microscope image showing the polyolefin porous membrane of Example 4. Figure 5 is a scanning electron microscope image showing the polyolefin porous membrane of Example 5. Figure 6 is a scanning electron microscope image showing the polyolefin porous membrane of Example 6. Figure 7 is a scanning electron microscope image showing the polyolefin porous membrane of Example 9. Specific details for implementing the invention

[0046] To clarify the purpose, technical solution, and advantages of the embodiments of the present invention, the technical solution of the embodiments of the present invention is described clearly and completely below. Where conditions are not specified in the embodiments, the work is performed under normal conditions or conditions recommended by the manufacturer. All reagents or equipment for which the manufacturer is not specified are ordinary products available on the market.

[0047] The inventors have discovered that the uniformity of the fiber structure of a polyolefin porous membrane is an important guarantee for the performance of the separator, and that the microfiber structural characteristics determine the macroscopic performance of the polyolefin porous membrane as a battery separator, wherein the uniformity of the fiber distribution and orientation determines the uniformity of the mechanical performance of the separator, and that if the polyolefin porous membrane possesses the following characteristics, isotropy of excellent mechanical performance can be obtained, and furthermore, higher safety can be achieved in battery applications.

[0048] When observing a 20,000x magnification SEM image of a network fiber structure, it has the following characteristics.

[0049] (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a diameter > 15 nm is (R_MD) 2 Satisfying <0.8, R_MD is obtained from Equation 1 below, and

[0050] Equation 1;

[0051] In the above equation, N is the quantity of fibers on the outermost surface within the observation area, each fiber is denoted by n, and θ n is the narrow angle between fiber n and the MD direction, and θ n It is obtained in a counterclockwise direction starting from the left direction in the MD direction, and the length value L of fiber n in μm units. n and cosθ n The product of is L n cosθ n and φ nis the diameter value of the fiber n in nm units.

[0052] (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a diameter > 15 nm is (R_TD) 2 Satisfying <0.8, R_TD is obtained from Equation 2 below, and

[0053] Equation 2;

[0054] In the above equation, N is the quantity of fibers on the outermost surface within the observed area, each fiber is denoted by n, and β n is the narrow angle between fiber n and the TD direction, and β n It is obtained in a counterclockwise direction starting from the upward direction in the TD direction, and the length value L of fiber n in μm units. n and cosβ n The product of is L n cosβ n and φ n is the diameter value of the fiber n in nm units.

[0055] In one solution, the provided polyolefin porous membrane is manufactured by wet stretching and has a network fiber structure;

[0056] When observing the SEM image of the above network fiber structure at 20,000x magnification, it has the following characteristics.

[0057] (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a diameter > 15 nm is (R_MD) 2 Satisfying <0.5, R_MD is obtained from Equation 1 below, and

[0058] Equation 1;

[0059] In the above equation, N is the quantity of fibers on the outermost surface within the observation area, each fiber is denoted by n, and θ n is the narrow angle between fiber n and the MD direction, and θ nIt is obtained in a counterclockwise direction starting from the left direction in the MD direction, and the fiber (n) length value L in μm units. n and cosθ n The product of is L n cosθ n and φ n is the diameter value of the fiber n in nm units.

[0060] (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a diameter > 15 nm is (R_TD) 2 Satisfying <0.5, R_TD is obtained from Equation 2 below, and

[0061] Equation 2;

[0062] In the above equation, N is the quantity of fibers on the outermost surface within the observed area, each fiber is denoted by n, and β n is the narrow angle between fiber n and the TD direction, and β n It is obtained in a counterclockwise direction starting from the upward direction in the TD direction, and the length value L of fiber n in μm units. n and cosβ n The product of is L n cosβ n and φ n is the diameter value of the fiber n in nm units.

[0063] [Polyolefin Resin]

[0064] The polyolefin resin used as a raw material may be, for example, polyethylene, polypropylene, etc. Polyethylene is not particularly limited and various types of polyethylene may be used; for example, ultra-high molecular weight polyethylene (UHMwPE), high-density polyethylene (HDPE), medium-density polyethylene, branched low-density polyethylene, straight-chain low-density polyethylene, etc. may be used.

[0065] In addition, polyethylene may be a homopolymer of ethylene or a copolymer of ethylene and other α-olefins. The α-olefins may be, for example, propylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, octene, vinyl acetate, methyl methacrylate, styrene, etc.

[0066] In this specification, the polyolefin porous membrane refers to a microporous membrane having a polyolefin resin as the main component, and is, for example, a microporous membrane in which the polyolefin resin accounts for 90 mass% or more of the total amount of the microporous membrane. Hereinafter, the physical properties of the polyolefin porous membrane of the present embodiment will be described.

[0067] [MD / TD Tensile Strength Ratio]

[0068] The ratio of tensile strength in the MD direction and the TD direction of the polyolefin porous membrane of the present invention, i.e., the MD / TD tensile strength ratio, is selectably 0.8 or higher and 1.2 or lower. When the tensile strength ratio is within the above-described range, the force can be received more uniformly against impact in all directions, so the impact resistance applied to batteries as a separator is improved, it is more stable, and film breakage and short circuits can be suppressed.

[0069] When considering battery applications from the perspective of greater safety and stability, the MD / TD tensile strength ratio can be selected to be close to 1. In this case, since the strength of the polyolefin porous membrane has no directional dependence, when stress is applied to the film, it exhibits excellent toughness, does not crack in a specific direction, and can prevent the enlargement of through-holes even if foreign substances penetrate the microporous membrane. On the other hand, if the tensile strength in the MD direction is too high, tearing in the MD direction may occur. If the tensile strength in the TD direction is too high, tearing in the TD direction or detachment of the bond at the electrode tab adhesive portion may easily lead to a short circuit.

[0070] [MD / TD Break Elongation Ratio]

[0071] The ratio of the elongation at break in the MD direction and the TD direction of the polyolefin porous membrane of the present invention, i.e., the MD / TD elongation at break ratio, is selectably 0.8 or higher and 1.2 or lower. When the elongation at break ratio is within the above-described range, the force can be received more uniformly against impact in all directions, so the impact resistance applied to batteries as a separator is improved, it is more stable, and film breakage and short circuits can be suppressed.

[0072] In terms of being safer and more stable for battery applications, the MD / TD elongation at break ratio is selectably close to 1. Since the strength of the polyolefin microporous membrane has no directional dependence, when stress is applied to the film, it has excellent toughness, does not crack in a specific direction, and can prevent the enlargement of the through hole even if foreign substances penetrate the microporous membrane.

[0073] [Film Thickness]

[0074] The thickness of the polyolefin porous membrane is not particularly limited. In terms of film strength, the thickness of the polyolefin porous membrane of the present invention is 2 μm or more, optionally 5 μm or more. In addition, in terms of permeability, the thickness of the microporous membrane is 50 μm or less, optionally 30 μm or less.

[0075] [tensile strength]

[0076] The tensile strength of the polyolefin porous membrane of the present invention is 150 MPa or more in both MD and TD directions, optionally 200 MPa or more. If the tensile strength is weak, battery winding performance deteriorates, or short circuits easily occur due to battery crash tests performed from the outside, foreign substances inside the battery, etc. In addition, the upper limit of the tensile strength in the MD direction and TD direction is not specifically limited, and according to actual production experience, the upper limit of the tensile strength in the MD direction and TD direction is optionally 700 MPa or less, optionally 600 MPa or less, and optionally 550 MPa or less.

[0077] [Break Elongation]

[0078] The elongation at break in the MD direction and the TD direction of the polyolefin porous membrane of the present invention is, for the most part, 90% or more. When the elongation at break is within the above-described range, the flexibility is utilized to suppress the occurrence of film breakage and short circuits in the separator when an impact is applied within the battery. Furthermore, the upper limit of the elongation at break in the MD direction and the TD direction is not specifically limited, but is, for example, 400% or less, optionally 300% or less, and optionally 200% or less. When the elongation at break is within the above-described range, when the electrode is wound, the separator is stretched and does not deform, and the windability is good.

[0079] The MD and TD elongation at break is optionally 10 to 200%, optionally 10 to 150%, and optionally 10 to 120%, respectively. A microporous membrane with MD and TD elongation at break within the aforementioned ranges not only has good battery winding properties but is also resistant to deformation during battery crash tests.

[0080] [Thermal Shrinkage Rate]

[0081] As a separator, the polyolefin porous membrane must also possess excellent thermal shrinkage characteristics at high temperatures; for example, it exhibits excellent results in high-temperature storage tests, high-temperature cycle tests, and baking tests when manufactured into a battery.

[0082] In terms of dimensional stability of the separator during the charge / discharge process, the thermal shrinkage rate in the MD direction is less than 5% and the thermal shrinkage rate in the TD direction is less than 6.5%, optionally, the MD thermal shrinkage rate is 4% or less and the TD thermal shrinkage rate is 4% or less, optionally, the MD thermal shrinkage rate is 3% or less and the TD thermal shrinkage rate is 2.5% or less, optionally, the MD thermal shrinkage rate is 1% or less and the TD thermal shrinkage rate is 1% or less. If the thermal shrinkage rate is greater than the above-described selectable range, it is undesirable because the microporous membrane is prone to shrinking in the width direction during the battery drying process, battery high-temperature cycle test, battery high-temperature storage test, etc.

[0083] [Method for manufacturing a polyolefin porous membrane]

[0084] The polyolefin porous membrane of the present invention is manufactured by wet stretching, and the method of manufacturing the same comprises: (1) using one or more polyolefin resin materials as main raw materials, mixing the said raw materials with a pore-forming agent and an antioxidant, and extruding the mixture through a die to manufacture a cast sheet; (2) stretching the cast sheet in both directions to manufacture an oil film; and (3) extracting the oil film and then performing a heat-setting treatment.

[0085] Here, controlling the temperature and the stretching ratio during the stretching process of the cast sheet is one of the key factors in obtaining a polyolefin porous membrane having the characteristics described above; the temperature field and the stretching field must be controlled during the bidirectional stretching process, the temperature of the cast sheet material itself must not exceed 140°C, the temperature difference between different points in the stretching area temperature field must be less than 0.5°C, and the ratio of the stretching ratio in the MD direction to the stretching ratio in the TD direction must be between 0.9 and 1.1, and when the actual stretching ratio is within the range described above, the tensile strength or elongation at break of the obtained polyolefin porous membrane is well balanced in the MD direction and the TD direction, thereby further improving film strength and impact resistance.

[0086] Next, during the heat setting process, the original stretching ratio relationship in the MD and TD directions must be maintained, and the second key element is that the stretching ratio ratio of the MD direction and the stretching ratio in the TD direction during the heat setting process is the stretching ratio ratio of the bidirectional stretching in step (2), i.e., 0.9 or more and 1.1 or less.

[0087] Here, the stretching ratio in the MD direction and the stretching ratio in the TD direction are the stretching ratio in the MD direction and the actual stretching ratio in the TD direction of the actual membrane.

[0088] In the case of simultaneous stretching, the stretching ratio in the MD direction and the stretching ratio in the TD direction can be obtained directly by the actual equipment settings or in the following manner. Since the simultaneous stretching ratio in the MD direction is equal to the ratio of the velocity of the oil film produced after simultaneous stretching in the MD direction to the moving velocity of the sheet material before entering stretching; and since the simultaneous stretching ratio in the TD direction is equal to the ratio of the width of the oil film produced after simultaneous stretching in the TD direction to the width of the TD stretching area of ​​the sheet material before entering stretching, care must be taken to reduce the width and length of the clamping portion of the clip.

[0089] In the case of asynchronous stretching, the stretching ratio in the asynchronous MD direction can be obtained directly by the actual equipment setting, or by the ratio of the sheet material speed and the speed before stretching after stretching in the MD direction and before entering TD stretching; the stretching ratio in the asynchronous TD direction is the ratio of the actual width of the oil film after TD stretching is completed and the actual width of the gel sheet material before MD stretching.

[0090] As long as the method for manufacturing the polyolefin porous membrane described above can obtain a polyolefin porous membrane having the characteristics described above, the types and mixing ratios of the polyolefin, pore-forming agent, and antioxidant, the method of mixing and extrusion, the type and use of an extractant, and the process for mitigating heat setting are not particularly limited.

[0091] The polyolefin resin used as a raw material may be, for example, polyethylene, polypropylene, etc. Polyethylene is not particularly limited and various types of polyethylene may be used, for example, ultra-high molecular weight polyethylene (UHMWPE), high-density polyethylene (HDPE), medium-density polyethylene, branched low-density polyethylene, straight-chain low-density polyethylene, etc. In addition, polyethylene may be a homopolymer of ethylene or a copolymer of ethylene and other α-olefins. The α-olefin may be, for example, propylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, octene, vinyl acetate, methyl methacrylate, styrene, etc.

[0092] In terms of facilitating the processing of the polymer melt and preventing film breakage, the viscosity average molecular weight of the polyolefin resin is 200,000 or more and 5 million or less; when the viscosity average molecular weight of the polyolefin resin is within the above-mentioned range, the film forming performance is good.

[0093] In addition, the film-forming material may include polymers of resin components other than polyolefin materials as needed, and high-temperature resistant resins such as polypropylene, polyimide, polyamide, fluoropolymer, etc. may be used. Here, the mass ratio of polyolefin in the mixture is ≥15%, and the mass ratio of high-temperature resistant resin in the mixture is <10%.

[0094] Here, the pore-forming agent may be a liquid hydrocarbon mixture such as white oil, an organic acid ester such as dioctyl phthalate (DOP), an inorganic ester such as trioctyl phosphate (TOP), an organic material capable of forming a homogeneous solution with a polyolefin resin, or a mixture of the various pore-forming agents described above.

[0095] Here, the antioxidant may be used as a single main antioxidant or as a combination of various antioxidants. Adding an antioxidant can mitigate the aging and degradation of the polymer and pore-forming agent during the shearing process, and effectively improve the color, flatness, and strength of the film surface.

[0096] The stretching temperature is optionally within a range above the softening point (Tcd) of a mixture in which the polyolefin resin and the pore-forming agent are sufficiently melted, and below the melting point of the polyolefin resin. Furthermore, the melting point of the polyolefin resin refers to the melting point of the polyolefin resin in the gel-like sheet material. When the stretching temperature is below the melting point of the polyolefin resin, the melting of the polyolefin resin in the gel-like sheet material is suppressed, and the molecular chains can be effectively oriented by stretching. In addition, when the stretching temperature is above the softening point (Tcd), the polyolefin resin in the gel-like sheet material is sufficiently softened, and the stretching tension can be reduced, thereby improving film forming performance, suppressing film breakage during stretching, and enabling stretching at a high magnification. The stretching temperature can be set, for example, to 50°C or higher and 140°C or lower, and optionally to 60°C or higher and 130°C or lower. Here, the stretching temperature refers to the temperature of the gel sheet material.

[0097] By controlling and reducing the difference in orientation during the stretching process of the separator and controlling the molding temperature, it is possible to obtain a polyolefin porous membrane with a uniform orientation of the microfiber structure and, furthermore, a small difference in macroscopic bidirectional mechanical performance. When used as a separator for batteries, this can improve the stability of the separator in battery production and the safety of the separator in battery applications.

[0098] Examples

[0099] The present invention will be described in detail below through examples. It should be noted that the present invention is not limited by these examples.

[0100] Example 1

[0101] Using 25 parts by weight of polyethylene powder (GUR4116, Ticona Celanese), 5 parts by weight of polypropylene (T30S, Zhenhai Refinery), and 70 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the polyolefin composition and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0102] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0103] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 120°C at a speed of 40 m / min, with stretching at a magnification of 6.5x in both the MD and TD directions. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the MD drawing action, and since the shrinkage was 15%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of stretching in the MD direction to stretching in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0104] Example 2

[0105] Using 23 parts by weight of ultra-high molecular weight polyethylene powder (GUR4012, Ticona Celanese) and 77 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0106] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0107] A sheet material, namely a cast sheet, was drawn and stretched. Rapid stretching was performed at 117°C at a speed of 40 m / min, with stretching at a magnification of 7.5x in the MD direction and 7.2x in the TD direction. During stretching, the uniformity of the temperature field must be controlled, and the temperature difference between different points in the temperature field of the stretching area must be less than 0.3°C. After stretching, an oil film was prepared. The oil film was placed in dichloromethane for extraction, and the paraffin oil within the oil film was extracted.

[0108] Next, the dichloromethane remaining in the membrane was removed by a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to MD drawing action, and since the shrinkage was 18%, heat setting and width expansion were performed again at 131°C to reach the original ratio of the stretching ratio in the MD direction to the stretching ratio in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0109] Example 3

[0110] Using 15 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 5 parts by weight of high-density polyethylene powder (GUR4116, Ticona Celanese), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0111] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0112] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 122°C at a speed of 40 m / min, with a magnification of 7.2x in the MD direction and 7.1x in the TD direction. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the MD drawing action, and since the shrinkage was 20%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0113] Example 4

[0114] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0115] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0116] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 117°C at a speed of 40 m / min, with a magnification of 6.8x in both the MD direction and the TD direction. The uniformity of the temperature field during stretching had to be controlled, ensuring that the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, thereby extracting the paraffin oil within the film. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction; since this shrinkage was 21%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, ultimately yielding a polyolefin porous membrane with a uniform fiber structure orientation.

[0117] Example 5

[0118] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0119] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0120] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 116°C at a speed of 40 m / min, with 8x stretching in both the MD direction and the TD direction. The uniformity of the temperature field during stretching had to be controlled, ensuring that the temperature difference between different points in the stretching zone temperature field was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, thereby extracting the paraffin oil within the film. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the MD direction drawing action, with a shrinkage of 21%. Consequently, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of stretching in the MD direction to stretching in the TD direction, ultimately yielding a polyolefin porous membrane with a uniform fiber structure orientation.

[0121] Example 6

[0122] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0123] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0124] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 115°C at a speed of 40 m / min, with a magnification of 10x in both the MD direction and the TD direction. The uniformity of the temperature field during stretching had to be controlled, ensuring that the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, thereby extracting the paraffin oil within the film. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction; since this shrinkage was 21%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, ultimately yielding a polyolefin porous membrane with a uniform fiber structure orientation.

[0125] Example 7

[0126] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0127] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0128] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 115°C at a speed of 40 m / min, with stretching at a magnification of 10x in the MD direction and 11x in the TD direction. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction; since the shrinkage was 21%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of stretching magnification in the MD direction to stretching magnification in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0129] Example 8

[0130] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0131] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0132] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 115°C at a speed of 40 m / min, with a magnification of 10x in the MD direction and 9.1x in the TD direction. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the membrane was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction; since the shrinkage was 21%, the membrane underwent heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0133] Example 9

[0134] Using 15 parts by weight of ultra-high molecular weight polyethylene powder (VH200U, LPIC), 5 parts by weight of high-density polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0135] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0136] The sheet material, i.e., the cast sheet, was drawn and stretched stepwise. At 90°C, the cast sheet material was stretched in the MD direction, where the MD direction stretching ratio was 9x; then, at 119°C, it was rapidly stretched in the TD direction at a speed of 60 m / min, with a TD direction stretching ratio of 8.3x (the ratio of the exit width to the original cast sheet width is 8.2x). The uniformity of the temperature field during stretching must be controlled, and the temperature difference between different points in the temperature field of the stretching area must be less than 0.3°C, and an oil film was prepared after stretching. The oil film was placed in dichloromethane for extraction, and the paraffin oil within the oil film was extracted. Then, the dichloromethane remaining in the separator was removed by a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction, and since the shrinkage was 22%, heat setting at 131°C and width expansion were performed again to reach the ratio of the original stretching ratio in the MD direction to the stretching ratio in the TD direction, thereby finally obtaining a polyolefin porous membrane with a uniform fiber structure orientation.

[0137] Comparative Example 1

[0138] Using 25 parts by weight of ultra-high molecular weight polyethylene powder (GUR4116, Ticona Celanese) and 77 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0139] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0140] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 117°C at a speed of 40 m / min, with a magnification of 7.9x in the MD direction and 6.5x in the TD direction. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the separator was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the MD drawing action, and since the shrinkage was 18%, the material was subjected to heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, thereby finally obtaining a polyolefin porous membrane.

[0141] Comparative Example 2

[0142] Using 5 parts by weight of ultra-high molecular weight polyethylene powder (GUR2122, Ticona Celanese), 10 parts by weight of high-density polyethylene powder (VH200U, KPIC), 5 parts by weight of polyethylene powder (VH035, KPIC), and 80 parts by weight of paraffin oil (60#, Zhejiang Zhengxin), 0.3 parts by weight of an antioxidant (Irg1010 (Ciba Specialty Chemicals BASF)) and 0.1 parts by weight of an antioxidant (P168 (Ciba Specialty Chemicals Inc.)) were added to a total of 100 parts by weight of the high molecular weight polyethylene and paraffin oil, and mixed sequentially. After mixing the auxiliary agents, the ultra-high molecular weight polyethylene material was fed into a twin-screw extruder together with the paraffin oil and mixed to finally produce a molten gel mixture.

[0143] The gel was extruded using a T-die, the extruded melt temperature was controlled to 220°C or lower, and then rapidly cooled on a isothermal metal double roller with a surface temperature of 15°C to roll into a sheet material with a thickness of 1.5 mm.

[0144] The sheet material, namely the cast sheet, was drawn and stretched. Rapid stretching was performed at 116°C at a speed of 40 m / min, with a magnification of 7.1x in the MD direction and 5.4x in the TD direction. The uniformity of the temperature field during stretching had to be controlled, and the temperature difference between different points in the temperature field of the stretching zone was less than 0.3°C. After stretching, an oil film was prepared. The oil film was immersed in dichloromethane for extraction, and the paraffin oil within the film was extracted. Subsequently, the dichloromethane remaining in the separator was removed using a constant temperature hot air at 40°C. During the extraction and drying process, a small amount of shrinkage occurred in the TD direction due to the drawing action in the MD direction; since the shrinkage was 21%, the material underwent heat setting and width expansion at 131°C to reach the original ratio of the stretching magnification in the MD direction to the stretching magnification in the TD direction, thereby finally obtaining a polyolefin porous membrane.

[0145] Evaluation Method

[0146] (1) Film thickness test

[0147] The thickness of the polyolefin porous membrane obtained in the example was tested using a micrometer.

[0148] (2) Fiber orientation test

[0149] SEM images of a polyolefin porous membrane at 20,000x magnification were obtained using the Nova Nano SEM 450 field emission scanning electron microscope from FEI, USA, and observed with a circle with a radius of 1,000 nm as the observation area.

[0150] By the above-described Equations 1 and 2, the fiber orientation result R_MD in the MD direction and the fiber orientation result R_TD in the TD direction of the polyolefin porous membrane were obtained.

[0151] In addition, when calculating R_MD and R_TD, the fiber taken is a fiber on the outermost surface of a polyolefin porous membrane, N is the number of fibers on the outermost surface within the observation area, each fiber is denoted by n (n is a natural number), the fiber length taken indicates that a section of the same thickness having the same stretching direction in the same fiber is one length, and if the thickness of the same fiber changes, it is not calculated as one length and must be corrected in a timely manner, the same thickness section indicates that the increase in the width of the narrowest part relative to the width of the thickest part within the section is within 5%, the fiber diameter indicates the average value of the width of the widest part and the width of the narrowest part in the same thickness section, and the angle between the fiber and the MD direction or TD direction is the angle between the stretching direction of the same thickness section and the MD direction or TD direction.

[0152] (3) Tensile strength test

[0153] Tests were performed in accordance with the requirements of GB 1040.3-2006, and samples were prepared using a cutting method. The sample type is Type 2. A long-rod type with a length of 200 mm and a width of 25 mm was used, the jig distance was (100±5) mm, and the test speed was (250±10) mm / min.

[0154] (4) Elongation test

[0155] Tests were performed in accordance with the requirements of GB 1040.3-2006, and samples were prepared using a cutting method. The sample type is Type 2. A long-rod type with a length of 200 mm and a width of 25 mm was used, the jig distance was (100±5) mm, and the test speed was (250±10) mm / min.

[0156] (5) Thermal shrinkage rate test

[0157] Test according to the requirements of GB / T12027-2004, take a 100mm × 100mm sample from a polyolefin microporous membrane, place it in a blower oven, and leave it at 105℃ for 1 hour, and obtain the thermal shrinkage rate from the following formula.

[0158] MD Thermal Shrinkage Rate (%) = |(MD Length Before Heating - MD Length After Heating) ÷ MD Length Before Heating| × 100

[0159] TD Thermal Shrinkage Rate (%) = |(TD Length Before Heating - TD Length After Heating) ÷ TD Length Before Heating| × 100

[0160] Referring to Tables 1 and 2, the performance test results of the above examples and comparative examples are as follows.

[0161] Table 1: Relevant performance parameter indices of polyolefin porous membranes of Examples 1–9

[0162]

[0163] Table 2: Relevant performance parameter indices of polyolefin porous membranes of Comparative Examples 1 and 2

[0164]

[0165] Tables 1 and 2 are relevant performance indicators for the polyolefin porous membranes of Examples 1–9 and Comparative Examples 1–2, respectively, where R_MD is the result of fiber orientation in the MD direction in the polyolefin porous membrane (R_MD) 2 Satisfying <0.8, and the fiber orientation result in the TD direction is R_TD (R_TD) 2 If <0.8 is satisfied, it can be seen that the separator can obtain isotropy of excellent mechanical performance, thereby providing higher safety in battery applications.

[0166] The foregoing description is merely an optional embodiment of the present invention and is not intended to limit the invention; those skilled in the art will be aware that various modifications and variations are possible. All modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

Claim 1 A polyolefin porous membrane, wherein the polyolefin porous membrane has a network fiber structure; and the polyolefin porous membrane is characterized by having the following characteristics when observing an SEM image of the network fiber structure at 20,000x magnification. (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a fiber diameter > 15 nm is (R_MD) 2 Satisfying <0.8, R_MD is obtained from Equation 1 below, and Equation 1; in the above equation, θn is the angle between the fiber and the MD direction, θn is obtained starting from the left direction in the MD direction and in a counterclockwise direction, the product of the fiber length value Ln in μm and cosθn is Lncosθn, and φn is the fiber diameter value in nm (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a fiber diameter > 15 nm is (R_TD) 2 Satisfying <0.8, R_TD is obtained from Equation 2 below, and Equation 2; in the above equation, βn is the angle between the fiber and the TD direction, βn is obtained in a counterclockwise direction starting from the upward direction in the TD direction, the product of the fiber length value Ln in μm and cosβn is Lncosβn, and φn is the fiber diameter value in nm. Claim 2 In claim 1, the polyolefin porous membrane has a network fiber structure; and when observing an SEM image of the network fiber structure at 20,000x magnification, the polyolefin porous membrane has the following characteristics. (1) In a circle with a radius of 1000 nm, the fiber orientation R_MD in the MD direction of a fiber with a fiber diameter > 15 nm is (R_MD) 2 Satisfying <0.5, R_MD is obtained from Equation 1 below, and Equation 1; in the above equation, θn is the angle between the fiber and the MD direction, θn is obtained starting from the left direction in the MD direction and in a counterclockwise direction, the product of the fiber length value Ln in μm and cosθn is Lncosθn, and φn is the fiber diameter value in nm (2) In a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a fiber diameter > 15 nm is (R_TD) 2 Satisfying <0.5, R_TD is obtained from Equation 2 below, and Equation 2; in the above equation, βn is the angle between the fiber and the TD direction, βn is obtained in a counterclockwise direction starting from the upward direction in the TD direction, the product of the fiber length value Ln in μm and cosβn is Lncosβn, and φn is the fiber diameter value in nm. Claim 3 A polyolefin porous membrane according to claim 1 or 2, characterized in that the ratio of tensile strength in the MD direction to tensile strength in the TD direction, i.e., the MD / TD tensile strength ratio, is 0.8 ≤ MD / TD tensile strength ratio ≤ 1.

2. Claim 4 A polyolefin porous membrane according to claim 1 or 2, characterized in that the ratio of the elongation at break in the MD direction to the elongation at break in the TD direction, i.e., the MD / TD elongation at break ratio, is 0.80 ≤ MD / TD elongation at break ratio ≤ 1.

20. Claim 5 A polyolefin porous membrane according to claim 1 or 2, characterized in that the membrane thickness of the polyolefin porous membrane is 2 to 30 μm. Claim 6 A method for manufacturing a polyolefin porous membrane, wherein the polyolefin porous membrane has a network fiber structure; and when observing an SEM image of the network fiber structure at 20,000x magnification, the polyolefin porous membrane has the following characteristics, wherein (1) in a circle with a radius of 1,000 nm, the fiber orientation R_MD in the MD direction of a fiber with a fiber diameter > 15 nm is (R_MD) 2 Satisfying <0.8, R_MD is obtained from Equation 1 below, and Equation 1; in the above equation, θn is the angle between the fiber and the MD direction, θn is obtained in a counterclockwise direction starting from the left direction in the MD direction, the product of the fiber length value Ln in μm and cosθn is Lncosθn, and φn is the fiber diameter value in nm; (2) in a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a fiber diameter > 15 nm is (R_TD) 2 Satisfying <0.8, R_TD is obtained from Equation 2 below, and Equation 2; wherein βn is the angle between the fiber and the TD direction, βn is obtained in a counterclockwise direction starting from the upward direction in the TD direction, the product of the fiber length value Ln in μm and cosβn is Lncosβn, and φn is the fiber diameter value in nm; the manufacturing method comprises: Step 1: a step of manufacturing a cast sheet by mixing and extruding a polyolefin, a porogen, and an additive; Step 2: a step of stretching the cast sheet, wherein the temperature of the cast sheet material itself does not exceed 140℃ during the stretching process, the temperature difference between different points in the stretching region temperature field is less than 0.5℃, and the ratio of the stretching ratio in the MD direction to the stretching ratio in the TD direction, i.e., the MD / TD stretching ratio ratio, is 0.9 ≤ MD / TD stretching ratio ratio ≤ 1.1, thereby manufacturing an oil film; A method for manufacturing a polyolefin porous membrane characterized by including the step of: Step 3: extracting the oil film and then performing a heat-setting treatment, and maintaining the ratio of the stretching ratio in the MD direction and the stretching ratio in the TD direction of Step 2 through a width-enlarging stretching treatment during the heat-setting treatment. Claim 7 In claim 6, the polyolefin porous membrane has a network fiber structure; and when observing an SEM image of the network fiber structure at 20,000x magnification, the polyolefin porous membrane has the following characteristics, wherein (1) in a circle with a radius of 1,000 nm, the fiber orientation R_MD in the MD direction of a fiber with a fiber diameter > 15 nm is (R_MD) 2 Satisfying <0.5, R_MD is obtained from Equation 1 below, and Equation 1; in the above equation, θn is the angle between the fiber and the MD direction, θn is obtained in a counterclockwise direction starting from the left direction in the MD direction, the product of the fiber length value Ln in μm and cosθn is Lncosθn, and φn is the fiber diameter value in nm; (2) in a circle with a radius of 1000 nm, the fiber orientation R_TD in the TD direction of a fiber with a fiber diameter > 15 nm is (R_TD) 2 Satisfying <0.5, R_TD is obtained from Equation 2 below, and Equation 2; wherein, in the above equation, βn is the angle between the fiber and the TD direction, βn is obtained in a counterclockwise direction starting from the upward direction in the TD direction, the product of the fiber length value Ln in μm and cosβn is Lncosβn, and φn is the fiber diameter value in nm; the above manufacturing method comprises: Step 1: a step of manufacturing a cast sheet by mixing and extruding a polyolefin, a pore-forming agent, and an additive; Step 2: a step of stretching the cast sheet, wherein the temperature of the cast sheet material itself does not exceed 140℃ during the stretching process, the temperature difference between different points in the stretching region temperature field is less than 0.5℃, and the ratio of the stretching ratio in the MD direction to the stretching ratio in the TD direction, i.e., the MD / TD stretching ratio ratio, is 0.9 ≤ MD / TD stretching ratio ratio ≤ 1.1, thereby manufacturing an oil film; A method for manufacturing a polyolefin porous membrane characterized by including the step of: Step 3: extracting the oil film and then performing a heat-setting treatment, and maintaining the ratio of the stretching ratio in the MD direction and the stretching ratio in the TD direction of Step 2 through a width-enlarging stretching treatment during the heat-setting treatment. Claim 8 A method for manufacturing a polyolefin porous membrane according to claim 6 or 7, characterized in that, in step 2, the stretching ratio in the MD direction and the stretching ratio in the TD direction are both 5 times or more. Claim 9 A method for manufacturing a polyolefin porous membrane according to claim 6 or 7, characterized in that, in step 1, the mass ratio of the polyolefin in the mixture is ≥15% and the viscosity average molecular weight of the polyolefin is between 200,000 and 5 million. Claim 10 A method for manufacturing a polyolefin porous membrane according to claim 6 or 7, wherein the additive comprises an antioxidant, the mass ratio of the antioxidant in the mixture is 0 to 0.5%, and in step 1, the antioxidant is one or more of amines, sulfur-containing compounds, nitrogen-containing compounds, phosphorus-containing compounds, and organometallic salts. Claim 11 A method for manufacturing a polyolefin porous membrane according to claim 6 or 7, characterized in that the pore-forming agent is one or more of white oil, paraffin oil, and polyethylene glycol. Claim 12 A battery separator characterized by comprising a polyolefin porous membrane according to claim 1 or 2. Claim 13 A battery separator characterized by including a polyolefin porous membrane according to paragraph 3. Claim 14 A battery separator characterized by including a polyolefin porous membrane according to paragraph 4. Claim 15 An electrochemical device characterized by including a polyolefin porous membrane according to claim 1 or 2 as a device for separating the anode and the cathode. Claim 16 An electrochemical device characterized by including a polyolefin porous membrane according to paragraph 3 as a device for separating the anode and the cathode. Claim 17 An electrochemical device characterized by including a polyolefin porous membrane according to claim 4 as a device for separating the anode and the cathode. Claim 18 An electrochemical device characterized by including a battery separator according to claim 12 as a device for separating the positive and negative electrodes. Claim 19 An electrochemical device characterized by including a battery separator according to Clause 13 as a device for separating the positive and negative electrodes. Claim 20 An electrochemical device characterized by including a battery separator according to claim 14 as a device for separating the positive and negative electrodes.

Citation Information

Patent Citations

  • Successively Biaxial-Oriented Porous PolypropyleneFilm and Process for Production Thereof

    KR1020030080007A

  • Improved laminated multilayer membranes, separators, batteries, and methods

    KR1020180026790A

  • A porous separator member and a separator comprising the same

    KR1020210147681A

  • Polyolefin microporous membrane, separator for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    KR102126212B1